The cricket bowling performance of different racial groups at a junior provincial level in South Africa - Taliep, M S (South African Journal of Sports Medicine, 2015)
Objective. To investigate the difference in performance and bowling opportunity of black African (BA), coloured/Indian (C/I) and white (W) cricket bowlers at a junior provincial level in South Africa between 2006 and 2012. Methods. Data of all players performing in the South African interprovincial under-13 (U13), under-15 (U15) and under-19 (U19) tournaments were analysed. Bowling performance (bowling average and the top 20 wicket takers relative to their par representation) and bowling opportunity (number of overs bowled) were compared between racial groups. Results. There were no significant differences in the bowling averages between BA bowlers and the other racial groups between 2008 and 2012. BA bowling averages were only significantly worse than W bowlers in the U13s in 2006 and U19s in 2007. BA bowling averages were also only significantly worse than C/I in the U13s and U15s in 2007. BA bowlers were below par representation in the top 20 wicket takers in each year for the U15s and U19s and below par representation for the U13s in 2007 - 2009 and 2011. The performance of C/I and W bowlers was relatively similar across the age groups. BA players bowled significantly fewer overs than W bowlers in the U13s in 2006, in the U15s in 2007 and 2009 and in the U19s in 2006, 2007, 2010 and 2011. C/I bowlers bowled significantly fewer overs than W bowlers in the U13s in 2008 and 2009. Conclusion. The bowling averages of the different racial groups are similar. However, there were relatively few BA bowlers in the top 20 wicket takers each year. This could be because of a lack of highly skilled BA bowlers or the lack of opportunity provided to BA bowlers to bowl in these tournaments.